A Novel Signature of Lipid Metabolism-Related Gene Predicts Prognosis and Response to Immunotherapy in Lung Adenocarcinoma - Zhang, Kai; Qian, Ying; Quan, Xiaowei; Zhu, Tengteng; Qian, Biyun (Frontiers in Cell and Developmental Biology, 2022)
Background: Lipid metabolism disorder, a new hallmark of cancer initiation, has been involved in lung adenocarcinoma (LUAD). However, few biomarkers about lipid metabolism related genes (LMRGs) have been developed for prognosis prediction and clinical treatment of LUAD patients. Methods: In this study, we constructed and validated an effective prognostic prediction model for LUAD patients depending on LMRGs. Subsquently, we investigated the prediction model from immune microenvironment, genomic changes and immunotherapy. Results: Then, eleven LMRGs were identified and applied to the LUAD subtyping. In comparison with the high-risk group, the low-risk group exhibited a remarkably favorable prognosis, along with higher immune score and lower tumor purity. Moreover, the low-risk group presented higher levels of immune checkpoint molecules, lower Tumor Immune Dysfunction and Exclusion (TIDE) score and Tumor Mutant Burden (TMB) and higher likelihood of benefiting from immunotherapy. Furthermore, the genomic changes of 6 LMRGs (CD79A, HACD1, CYP17A1, SLCO1B3, ANGPTL4 and LDHA) were responsible for the difference in susceptibility to LUAD by greatly influencing B cell activation. Conclusions: Generally speaking, the LMRGs model is a reliable independent biomarker for predicting adverse outcomes in LUAD patients and have the potential to facilitate risk-stratified immunotherapy.